Synchronous Raman Spectroscopy Method for Measuring Strain-Charge Information of Graphene Materials - Hong, C.; Song, H.; Kang, Y.; Xie, H.; Qiu, W.; Du, H.; Han, B. (Experimental mechanics, 2023)
Background How to obtain deformation and charge information through in situ measurement of nanomaterial devices is a new and challenging problem, which are related in performance design and failure prevention. Objective To accurately measure the electro-mechanical influence on microelectronic devices, research on an in situ measurement method based on Raman spectroscopy is carried out. Methods Two analytical models are derived: the doublet vector method and the spectral approximation method. Then, a graphene electrode experiment is used to carry out synchronous in situ measurement of strain and charge density. Experimental data are further used to compare and analyze the approximation levels of the spectral approximation method under electro-mechanical field effect. Results The results show that when both strain and charge exist and one factor is very weak, the relative difference between the results of the doublet vector method and doublet approximation method, which considers both electrical and mechanical factors, is smaller. Conclusions The methods mentioned above can realize synchronous and separate measurement of graphene electronic devices, which can also provide methods for measuring and controlling the electromechanical properties of new-type electronic devices’ electro-mechanical information.